Peddling a semiotics of fear: a critical examination of scare tactics and commercial strategies in public health promotion - Brookes, Gavin; Harvey, Kevin (Taylor & Francis, 2015)
This study critically examines the ways in which the nationwide Diabetes UK/Tesco public health promotion campaign (2013-2014) sought to raise awareness of Type 2 diabetes. Conducting a multimodal critical discourse analysis of six campaign images, we identify the presence of fear-inducing, stigmatising and commercial strategies, through which the campaign emphasises the dangers of diabetes and advocates personal responsibility for assessing both individual and others’ risk of the disease. Specifically, three discursive techniques are deployed in this campaign to achieve these ends: (1) the depiction of grief and amplification of diabetes-related danger, (2) the promotion of diabetes risk and responsibilization of individuals for their health, and (3) the commercial branding and framing of the Diabetes UK/Tesco partnership as providing tools for diabetes prevention and management. Our findings raise concerns about the moral legitimacy of using fear-inducing and commercial strategies in public health campaigns, strategies which do little to address the environmental factors which are associated with increasing rates of the disease.